Retrograde Transpubic Approach for Percutaneous Radiofrequency Ablation and Cementoplasty of Acetabular Metastasis - Salem Bauones; Veronique Freire; Thomas P. Moser (Case Reports in Radiology)
We report a case of painful and disabling anterior acetabular bone metastasis treated with bipolar radiofrequency ablation and cementoplasty. Due to the high risk of complications related to the proximity of the femoral neurovascular structures with a direct approach, we successfully performed a retrograde transpubic approach under combined CT and fluoroscopic guidance. In the present report, we describe this approach detailing its indications, advantages, and the technical tips to achieve a safe and satisfactory procedure.